2018
DOI: 10.1038/s41598-018-35797-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia impaired cognitive and memory functions in obese patients with obstructive sleep apnoea

Abstract: Obstructive sleep apnoea (OSA) is a sleep disorder involving repeated nocturnal desaturation and sleep fragmentation. OSA can result in decreased daytime alertness and neurocognitive dysfunction. Hypercapnia status is also related to neurocognitive dysfunction in patients with pulmonary diseases. We evaluated the effects of hypercapnia on cognitive performance and memory function in a prospective case-controlled study. We enrolled thirty-nine obese patients with OSA and collected their arterial blood samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…Previous obstructive sleep apnoea studies have supported a correlation between hypoxemia/hypercapnia and delirium or cognitive impairment 25 . This was not supported by our study, but might be due to low power from POCD occurring rarely in our population, or the fact that the development of POCD is multifactorial including other factors than hypoxemia such as impaired sleep, opioid use 17 and inflammation 26 .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Previous obstructive sleep apnoea studies have supported a correlation between hypoxemia/hypercapnia and delirium or cognitive impairment 25 . This was not supported by our study, but might be due to low power from POCD occurring rarely in our population, or the fact that the development of POCD is multifactorial including other factors than hypoxemia such as impaired sleep, opioid use 17 and inflammation 26 .…”
Section: Discussioncontrasting
confidence: 73%
“…3,24 Previous obstructive sleep apnoea studies have supported a correlation between hypoxemia/hypercapnia and delirium or cognitive impairment. 25 This was not supported by our study, but might be due to low power from POCD occurring rarely in our population, or the fact that the development of POCD is multifactorial including other factors than hypoxemia such as impaired sleep, opioid use 17 and inflammation. 26 Among other clinical outcomes of specific interest are cardiac injury, which a recent study in abdominal surgery have suggested to correlate with hypoxemia, 3 similar to previous studies observing ischaemic ECG changes during post-operative hypoxemic episodes.…”
Section: Discussionmentioning
confidence: 56%
“…[38][39][40] Similarly, OSA-related chronic intermittent hypoxia and hypercapnia can also hinder attention, memory and cognition. 41,42 Specifically, how SPD generates cognitive and behavioural dysfunction is still unclear. A large number of cortisol production induced by hypothalamic-pituitary-adrenal axis hyperactivity may be a possible mechanism that explains how SPD influences cognitive and behavioural dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…3941 Recent findings in subjects with OSA suggest that in addition to sleep fragmentation and hypoxemia, hypercapnia may be a key driver of neurocognitive decline. 42,43 The present findings raise the intriguing possibility that transient and chronic hypercapnia may contribute to such cognitive deficits at least in part through the impairment of perivascular clearance of interstitial solutes.…”
Section: Discussionmentioning
confidence: 69%